A comparative analysis on the framing of politics in Jordanian online news - Almomani Mohammad Hamzeh Mohammad,; Loh, Yoke Ling (Penerbit Universiti Kebangsaan Malaysia, 2023)
News bias has a detrimental impact on how the general public and specific individuals perceive the news information, resulting in a significant impact on Jordanian politics. Mainstream media sources continue to be the main sources of information about current events in Jordan, despite the internet's many advancements in the domains of communication. The widespread usage of news polarisation and the interference of the government through laws and policies are two additional reasons why it is regarded as good journalism in Jordan. Through a descriptive and comparative content analysis, this research applies theoretical fieldwork of communication and aims to comprehend and assess how the Al Hamzeh issue was framed in the Jordanian online news agencies, Al Ghad and Al Rai. The results of this study show that the official online news agency Al Rai gave more attention in its coverage of the Al Hamzeh issue than the independent online news Al Ghad. Al Ghad and Al Rai news pieces extensively implement the five different types of news frames in both their headlines and body copy. Additionally, the wording employed in the chosen news stories had a strong slant. The outcome regarding the independent news agency, Al Ghad, interpret contradiction anent news independence in Jordan. This study advances development of knowledge in the areas of press freedom, foreign policy, and communication. This study clarifies the understanding of Jordan's media landscape.